Bioequivalence Study of Generic Tablet Formulations Containing Ethinylestradiol and Chlormadinone Acetate in Healthy Female Volunteers - Bonn, Michael; Eydeler, Urte; Barkworth, Martin; C. Rovati, Lucio (Arzneimittelforschung, 2009)
The bioavailability and bioequivalence of two different film coated tablets containing ethinylestradiol (CAS 57-63-6) and Chlormadinone acetate (CAS 302-22-7) (Bellissima® as test and the respective preparation from the originator as reference) were investigated in 20 healthy female volunteers after oral single-dose administration. The study was performed according to a single-center, randomised, single-dose, 2-way cross-over design with a wash-out phase of 28 days. Blood samples for pharmacokinetic profiling were taken up to 168 h post-dose, and ethinylestradiol and Chlormadinone acetate plasma concentrations were determined with a validated LC-MS/MS method. The observed mean maximum plasma concentrations (Cmax) of ethinylestradiol were 124.96 pg/ml (test) and 129.12 pg/ml (reference). In the case of Chlormadinone acetate, Cmax averaged 6.9566 ng/ml (test) and 6.6663 ng/m (reference). The geometric means of area under the plasma concentration-time curve (AUC0–∞) of ethinylestradiol were 1292.35 pg/mlh (test) and 1380.49 pg/ml · h (reference). For Chlormadinone acetate, geometric means of AUC0–∞ were 53.322 ng/ml · h (test) and 58.111 ng/ml · h (reference). The median of tmax of ethinylestradiol was 1.5 h for both test and reference and the median of tmax of Chlormadinone acetate 1.0 h (test) and 1.5 h (reference). Plasma elimination half-lives (t1/2) of ethinylestradiol were 14.96 h (test) and 15.41 h (reference) and of Chlormadinone acetate 56.63 h (test) and 56.17 h (reference), respectively. Both primary target parameters AUC0–∞ and Cmax were tested parametrically by analysis of variance (ANOVA). The point estimator and the 90 % confidence intervals for the AUC0–∞ ratio (test/reference: 93.72% [86.62%–101.39%]) indicate high similarity of both formulations with respect to the extent of ethinylestradiol exposure. A high degree of similarity was also observed for Cmax of ethinylestradiol, as the point estimator and the 90 % confidence interval for the Cmax ratio are 96.18% (90.82%–101.86%). Regarding the AUC0–∞ ratio of Chlormadinone acetate, the point estimator is 91.60 % and the 90% confidence interval 84.08%–99.79 %. Furthermore, exchangeability of both formulations is also suggested by the point estimator and 90 % confidence of Cmax of this active agent (104.72% [95.76%–114.53%]). Bioequivalence between test and reference formulation was demonstrated since for both ethinylestradiol and Chlormadinone acetate all 90% confidence intervals of AUC0–∞ and Cmax fall into the generally accepted range of 80%–125%.
Keywords: Bellissima®; Bioequivalence; CAS 57-63-6; CAS 302-22-7; Chlormadinone acetate; Ethinylestradiol